Isolation and sequence of a human cytochrome P-450 cDNA clone. - Phillips, I R (1985)
A previously reported cDNA clone [pP450(1)] coding for a phenobarbital-inducible cytochrome P-450 variant of rat liver microsomal membranes, designated P-450e(U.C.), was used as a specific hybridization probe to screen a human liver cDNA library. Restriction mapping showed that two of the colonies isolated contained plasmids coding for overlapping regions of the same cDNA sequence. The clone [pHP450(1)] having the longer cDNA insert (1.25 kilobase pairs) was sequenced. The homology between the rat and human cDNAs is 62% in their coding regions but is only random (24%) in the 3'-noncoding nucleotides. The amino acid sequence deduced from the human cDNA is 50% identical to that of P-450e(U.C.). The homology increases to 72% if conservative changes in amino acid residues are permitted. The hydropathy profile of the polypeptide encoded by pHP450(1) is almost identical to that of P-450e(U.C.). Regions known to be highly conserved in cytochrome P-450 isozymes isolated from rat, rabbit, and mouse were found to be conserved in the amino acid sequence derived from pHP450(1). Analysis by Southern blotting indicated that the human cytochrome P-450 encoded by pHP450(1) is part of a multigene family.